A Study on Electroencephalography Findings of Patients Visiting the Psychiatric Clinic: An Experience at A Tertiary Care Center in Western Nepal - Sharma, Bhaskkar; Shrestha, Rajesh; Lamichhane, Ram Prasad (Journal of Lumbini Medical College, 2021)
Introduction: The electroencephalography (EEG) is the recording of brain’s spontaneous electrical activity over a period of time (20-40 minutes) recorded from multiple electrodes placed on the scalp. It is used in seizure disorder, organicity, and psychiatric conditions. There is a paucity of literature with regard to the application of EEG in various conditions in our setting. Methods: This was a cross-sectional study, where data of the patients who visited the EEG section of psychiatric clinic from September 15, 2019 to July 14, 2020 were collected retrospectively. The demographic details, EEG details, and the clinical details were recorded and analyzed. Results: A total of 110 patients underwent EEG during the study period. Of them, 61 (55.45%) had normal EEG. Among the patients with normal EEG, 60 (98.36%) had clinical history suggestive of seizure disorder. Of the rest 49 (44.55%) patients with abnormal EEG, 48 (97.96%) had history of seizure. Majority patients referred for EEG fell in the prime of their life (1-30yrs). Almost all (98.2%) patients with the history of seizure were taking anti-epileptic drugs. Conclusion: EEG is a common investigation done in psychiatric clinic. Nearly half of the patients with seizure disorders will have an abnormal EEG.